2005
DOI: 10.1007/s10620-005-2471-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Budd?Chiari Syndrome

Abstract: Thrombotic occlusion of the hepatic veins leads to liver dysfunction and liver failure requiring liver transplantation in advanced cases. The cause for the occlusion of the hepatic veins is not completely understood. However, several underlying conditions such as polycytemia, factor V Leiden mutation, and protein C and S deficiency are found in these patients. We here report our single-center experience with 18 consecutive patients with Budd-Chiari Syndrome (BCS) who were treated at our institution between Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…It is an uncommon disorder occurring in 1/100 000 of the general population worldwide (2). Nonetheless, if left untreated, BCS may lead to liver dysfunction and liver failure requiring liver transplantation in advanced cases (3). The prognosis of patients with BCS is difficult to predict.…”
mentioning
confidence: 99%
“…It is an uncommon disorder occurring in 1/100 000 of the general population worldwide (2). Nonetheless, if left untreated, BCS may lead to liver dysfunction and liver failure requiring liver transplantation in advanced cases (3). The prognosis of patients with BCS is difficult to predict.…”
mentioning
confidence: 99%
“…In cases of interventional treatment for hepatic venoocclusive lesions, the second hepatic hilum-occlusive HV should be reopened [9,10]. Open the connection and use a stent between the IVC and HV under the internal jugular vein (9/11) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 18 patients with BCS by Ruh et al (2005) revealed that myoproliferative disorders (groups of conditions that cause overproduction of blood cells, i.e., platelets, white blood cells, and red blood cells in the bone marrow) were common risk factors among the patients. This observation was corroborated by Slakey, Klein, Venbrux, and Cameron (2001), who noted that 22 of 54 reported cases involved myeloproliferative disorders.…”
Section: Etiologymentioning
confidence: 99%
“…Pregnancy is another risk factor, especially when the patient has an established thrombophilia history (Ruh et al, 2005). Behcet’s disease, an autoimmune disorder with recurrent thrombosis and vasculitis, and paroxysmal nocturnal hemoglubinuria are two additional established causes of BCS.…”
Section: Etiologymentioning
confidence: 99%